Variació oral. Reflexions sobre l’estudi de la llengua oral - Payrató, Lluís (Caplletra. Revista Internacional de Filologia, 1998)
Although modern linguistics has (theoretically) supported the primacy of the analysis of oral language over written texts, the comparison of studies based on the two kinds of analysis show the tradition of studies on many aspects of oraility. This paper, based on the statement above, presents a number of problems originated in the study of oral language and its different modes. The obstacles and difficulties are present during all stages of the research: from the data selection and collection (unthinkable without clear objectives) to problems dealing with the transcription and analysis of the data and to the limitation of variables, which are the essence of variation.